Strawberry Nectar Colour Stability and Aroma: Influence of Cultivar, Harvest Time and Ripening Stage - Helen Murray; Walter Brandes; Sezer Sari; Phillip Eder; Claudia Dietl-Schuller; Marlene Lindner; Christian Philipp; Heidi Halbwirth; Christian Haselmair-Gosch; Manfred Gössinger (Horticulturae, 2025)
This study investigated the impact of cultivar, harvest time, and ripening stage of strawberries on their aroma concentration and profile, and colour stability of nectars produced from these strawberries. Purees from 12 different cultivars from two countries, collected at different ripening stages and harvest times, were analysed. Furaneol and mesifuran content was analysed using a gas chromatography–flame ionisation detector (GC-FID), and gas chromatography–mass spectrometry (GC-MS) was used to determine the content of 12 aroma compounds, including esters, C6 compounds, and lactones. Nectars produced from these purees had their colour stability measured over 12 weeks. Both the colour and aroma were greatly influenced by strawberry cultivar. Within cultivars, nectars produced from strawberries that had been harvested overripe showed higher colour stability and higher concentrations of aroma compounds than those harvested ripe from an earlier harvest, although some cultivars were more affected by harvest time than ripening stage. Aroma compounds that correlated significantly (p < 0.05) with a good colour after storage included furaneol, ethyl butanoate, hexanal, γ-decalactone and γ-dodecalactone, as well as the total concentration of aroma compounds. Only γ-decalactone concentrations correlated significantly with overall nectar colour stability, although this could be due to cultivar effects.